Applications of MXene-based composite fibers in smart textiles. Issue 1 (February 2021) - Guo, Z; Li, Y; Lu, Z; Liu, W
Abstract: MXenes, a new family of early transition metal carbides or carbonitrides, have shown much promise over other 2D materials, due to the excellent conductivity, high power density, reliable cycling life and multifunctional applications. In general, the rich tunable surface terminations and chemical hydrophilicity of MXenes make them as attractive candidates in terms of energy-storage, sensors and shielding applications, especially in portable, wearable and flexible smart textiles. This review presents a brief phylogeny, synthesis, structural characteristics of MXene, and main applications of MXene-based composite in smart textiles, representing the tuning of properties for applications including fiber-based supercapacitors, sensors and electromagnetic shielding. Finally, the challenges and future perspectives of MXene in textiles are also considered.